Evaluation of X-ray protective shielding used in dental offices in Kerman, Iran, in 2014 - Jahangir Haghani (Journal of Oral Health and Oral Epidemiology, 2017)
BACKGROUND AND AIM: Protective equipment, such as lead aprons and thyroid shields, is effective in reducing patient radiation. This study was conducted for evaluation the use of thyroid shields and lead aprons in dental offices, in Kerman, Iran, in June 2014.